2004
DOI: 10.1590/s0103-84782004000600003
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência de Metarhizium anisopliae no controle do Percevejo-do-Colmo Tibraca limbativentris (Heteroptera: Pentatomidae) em lavoura de arroz irrigado

Abstract: O percevejo-do-colmo, Tibraca limbativentris Stal, 1860 (Heteroptera: Pentatomidae), é altamente prejudicial à cultura do arroz no Brasil, principalmente em sistemas de cultivo irrigados por inundação. O efeito de duas formas de aplicação, conídios em suspensão e veiculados em grãos de arroz autoclavado, da cepa (CP) 172 de Metarhizium anisopliae (Metsch.) Sorok., no controle do percevejo, foi avaliado em três experimentos conduzidos em 1991, 1993 e 1994, em lavoura comercial de arroz irrigado. Em 1991, tanto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
(11 reference statements)
1
13
0
8
Order By: Relevance
“…The rice stink bug, Tibraca limbativentris Stal, 1860 (Heteroptera: Pentatomidae), is one of the most serious pests attacking irrigated rice (Oryza sativa L.) crops worldwide, as it can cause yield losses up to 80 % when control measures are neglected (Ferreira et al, 1986;Martins et al, 2004). Metarhizium spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rice stink bug, Tibraca limbativentris Stal, 1860 (Heteroptera: Pentatomidae), is one of the most serious pests attacking irrigated rice (Oryza sativa L.) crops worldwide, as it can cause yield losses up to 80 % when control measures are neglected (Ferreira et al, 1986;Martins et al, 2004). Metarhizium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Metarhizium anisopliae (Metch.) Sorok (Ascomycota: Clavicipitaceae) complex has been observed causing epizootics on populations of T. limbativentris under irrigated conditions, and field trials with this fungus have shown promising results for the management of this pest in Brazil (Martins et al, 2004;Rampelotti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, biological control with the use of entomopathogenic fungi M. anisopliae (Metschnikoff) (Deuteromycetes) may be a viable alternative for the management of N. viridula and D. melacanthus in wheat. Several studies have shown that the fungus presented high pathogenicity to different species of bugs (SOSA-GÓMEZ; MOSCARDI, 1998;MARTINS et al, 2004;XAVIER;ÁVILA, 2006;RAMPELOTTI et al, 2007), especially to the sugarcane leafhopper, Mahanarva posticata (Stal, 1855) (Hemiptera: Cercopidae) (LOUREIRO et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the wide distribution of M. anisopliae in the ecosystem (soil) and its ability to infect a great number of insects, the use of this fungus as an alternative biological pest management tool has been suggested (Sung et al, 2007;Sandhu et al, 2012). Furthermore, natural infestations of M. anisopliae in stink bug species were reported (Xavier and Ávila 2006;Barbosa et al, 2015); this fungus was employed to control the sugarcane spittlebug Mahanarva posticata (Stal, 1855) (Hemiptera: Cercopidae) (Loureiro et al, 2012) and other pest stink bug species (Martins et al, 2004;Xavier and Ávila, 2006;França et al, 2006;Rampelotti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%